PENGARUH KESELAMATAN, KESAHATAN KERJA TERHADAP LINGKUNGAN KERJA DAN KINERJA KARYAWAN - Anggriani Husain; Margono Setiawan; Astrid Puspaningrum (Jurnal Aplikasi Manajemen, 2022)
The Objective of this study is to analyze the relationship between workplace safety, workplace health, working environment, and employee performance in the construction of mass rapid transit in jakarta by PT Hutama Karya (Persero). The Populasi of this quantitative study is 170 permanent employees who have been working for at lest one year in the company. In order to obtain dta from respondens who have certain information and have the characteristics expected by the researcher, purposive sampling was used (sugiyono, 2014). The data of this study was obtained from 170 respondents and was analyzed in PLS 3.0. the results of the analysis show that workplace safety and workplace health do not significantly influence employee performance. Therefore, this study asserts that working environment partially mediates the influence of workplace safety on employee performance and workplace health on employee performance. For future research, it is possible to further refine the research results by expanding and multiplying other variables and indicators that were not examined in this study. And can increase the number of respondents in the survey so that it can be generalized in a wider scope of research.